The Impact of the Customary Legal System on the Indonesian Legal System - Mahdi Rezaei; Leila Farzaneh; Alireza Ghaffari (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
This research discusses the impact of the customary law system on the Indonesian legal system. The customary law system has deep historical roots in Indonesian society and still has a significant influence on everyday life. Through a multidisciplinary approach, this research identifies how customary legal norms that have existed for a long time still play an important role in determining national legal policy. This impact can be seen in the implementation of laws, court decisions and government regulations that reflect customary legal values. The debate regarding official recognition of customary law norms and the role of customary institutions in law enforcement is an important part of this analysis.